Quadrophenia [videorecording (DVD)] - Roddam, Franc; Daniels, Phil; Ash, Leslie, 1960-; Davis, Philip, 1953-; Wingett, Mark, 1961-; Sting (Musician); Winstone, Ray, 1957-; Elphick, Michael, 1946-2002 (Criterion collection, 2012)
London, 1965: Like many other youths, Jimmy hates the philistine life, especially his parents and his job in a company's mailing division.